Financial Well-Being Gen Z: Eksplorasi Investment Interest, Materialisme, dan Financial Ignorance - Amelinda, Rita; Oktavini, Eva; Magdalena, Febriani Christina Susianti; Anwar, Roseline Mannuela (STIE Indonesia Banking School, 2025)
​This study investigates the influence of Investment Interest, Materialism, and Financial Ignorance on students' Financial Well-Being, with Propensity to Plan serving as a mediating variable. Data were collected from 185 students of the Faculty of Economics and Business in West Jakarta through questionnaires. The analysis employed Structural Equation Modeling (SEM) using SmartPLS 3.0 software.​ The findings reveal that Investment Interest and Materialism positively affect Propensity to Plan, whereas Financial Ignorance has a negative impact. Furthermore, Propensity to Plan significantly enhances Financial Well-Being. However, Investment Interest does not directly influence Financial Well-Being, underscoring the necessity of comprehensive financial planning to translate investment enthusiasm into tangible financial benefits. The relationships between Materialism and Financial Ignorance with Financial Well-Being exhibit complex dynamics, indicating the need for further research to understand the underlying mechanisms.​ Overall, the study emphasizes that meticulous financial planning and comprehensive financial education are crucial for achieving sustainable financial well-being.